2016
DOI: 10.1016/j.ijsu.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preoperative radiotherapy on stage IB2 and IIA2 cervical cancer: A retrospective cohort study

Abstract: Preoperative radiotherapy combined with radical surgery could improve locoregional control rate and would not increase the risk of postoperative complications. It may be a feasible treatment mode for early stage CC carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…In the past, studies compared the effects of preoperative radiotherapy or chemoradiotherapy on pathological outcomes. Tongqing Zhang et al [9] retrospectively analysed 80 patients who underwent preoperative radiotherapy and 90 stage IB2 and IIA2 cervical cancer patients who underwent radical surgery alone. Their results suggest that preoperative radiotherapy does not improve postoperative pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, studies compared the effects of preoperative radiotherapy or chemoradiotherapy on pathological outcomes. Tongqing Zhang et al [9] retrospectively analysed 80 patients who underwent preoperative radiotherapy and 90 stage IB2 and IIA2 cervical cancer patients who underwent radical surgery alone. Their results suggest that preoperative radiotherapy does not improve postoperative pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who receive surgery as the main treatment need to be classified based on postoperative pathological results to determine whether to supplement adjuvant therapy [7e10]; therefore, it is of practical significance to explore the effect of preoperative radiotherapy or chemoradiotherapy on postoperative pathological outcomes. Tongqing Zhang believes that preoperative radiotherapy does not improve postoperative pathology results [9]. Vizkeleti et al believe that preoperative radiotherapy significantly increases the rate of pathological complete remission and decreases the rate of positive surgical margins [10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that concurrent chemoradiotherapy can enhance the sensitivity of patients to radiotherapy [7], improve the 5-year survival rate, and increase the local control rate of tumors [8]. The mechanism may be as follows: 1.…”
Section: Discussionmentioning
confidence: 99%
“…Two retrospective studies, including 78 women with Stage IB2 and IIA cervical cancer and 171 with Stage IB2 and IIA2 cervical cancer, demonstrated that pre‐operative radiotherapy followed by radical surgery resulted in OS rates similar to, and locoregional tumor control higher than, those of radical surgery alone 9,10 . However, those two studies had a limited sample size and did not eliminate confounding factors such as tumor diameter and year of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In two retrospective studies of women with Stage IB2 and IIA cervical cancer, the rate of overall survival of women who underwent pre‐operative radiotherapy was not significantly different from that of women who underwent radical surgery directly, but the locoregional control rate of tumors was improved 9,10 . Another retrospective analysis of women with Stage IB1–IIB cervical cancer found no significant difference in the rate of 10‐year disease‐free survival (DFS) between those who underwent pre‐operative radiotherapy followed by radical surgery and those who underwent direct radical surgery 11 .…”
Section: Introductionmentioning
confidence: 95%